2010
DOI: 10.1016/j.cmet.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Signaling in Liver-Parenchymal Cells Suppresses Hepatic Inflammation and Improves Systemic Insulin Action

Abstract: The contribution of interleukin (IL)-6 signaling in obesity-induced inflammation remains controversial. To specifically define the role of hepatic IL-6 signaling in insulin action and resistance, we have generated mice with hepatocyte-specific IL-6 receptor (IL-6R) alpha deficiency (IL-6Ralpha(L-KO) mice). These animals showed no alterations in body weight and fat content but exhibited a reduction in insulin sensitivity and glucose tolerance. Impaired glucose metabolism originated from attenuated insulin-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 48 publications
13
149
1
2
Order By: Relevance
“…1E). Moreover, we also created IL-6Ra deficiency specifically in liver parenchymal cells (IL-6Ra L-KO mice) (17) and in the myeloid lineage (IL-6Ra…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1E). Moreover, we also created IL-6Ra deficiency specifically in liver parenchymal cells (IL-6Ra L-KO mice) (17) and in the myeloid lineage (IL-6Ra…”
Section: Resultsmentioning
confidence: 99%
“…To generate IL-6Ra-deficient (knockout; KO) mice (IL-6Ra KO mice), IL-6Ra floxed mice were crossed with deleter-cre mice, and offspring were intercrossed. IL-6Ra deficiency in liver parenchymal cells (IL-6Ra L-KO mice) was generated, as described previously (17). Myeloid lineage-specific IL-6Ra-deficient mice (IL-6Ra…”
Section: Generation Of Il-6ra-deficient Micementioning
confidence: 99%
See 1 more Smart Citation
“…31) IL-6 can function as anti-inflammatory wherein it inhibits lipopolysaccharideinduced TNF-α and IL-1, 43) and downregulate inflammatory signaling cascades that regulate fatty acid oxidation in obese/ diabetic condition. 44) Besides, increased IL-6 secretion in obesity is associated in correcting excess body weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In the same flow of thinking, IL-8 appears to have angiogenic effects 28,36,37 and IL-15, also produced by muscle contraction, seems to have anabolic effects and in the reduction of adiposity 36,37,86 . Although some studies do not show significant increases in the plasma IL-15 after exercise 87,88 , Tamura et al 89 observed this increase in individuals submitted to 30 minutes of exercise on a treadmill with an intensity of 70% of HRmax predicted by age (HRmax = 220 -age). The authors attribute the lack of consensus in the literature to the different experimental parameters and especially to the timing of the IL-15 measurement after exercise.…”
Section: Effect Of Physical Exercise In the Cytokine Productionmentioning
confidence: 99%